1991
DOI: 10.1177/026765839100700102
|View full text |Cite
|
Sign up to set email alerts
|

Parameter setting in second language phonology and syntax

Abstract: This paper reports on studies of second language acquisition in two domains, phonology and syntax. The phenomena investigated were the acquisition by native speakers of Hindi, Japanese, and Korean of two areas of English: in phonology, the mastery of particular syllable onset clusters, and in syntax, the acquisition of the binding patterns of reflexive anaphors. Both these areas are ones for which multi-valued parameters have been posited to account for the range of variation across natural languages. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 6 publications
3
118
0
Order By: Relevance
“…The identity preference in CQ speakers found here is consistent with previous work that shows a correlation between typology and synchronic asymmetries in individual speakers, particularly work examining sonority profiles in onsets (Greenberg and Jenkins 1964;Scholes 1966;Broselow and Finer 1991;Coleman and Pierrehumbert 1997;Moreton 2002;Davidson 2006Davidson , 2010Berent et al 2007;Berent and Lennertz 2010;Daland et al 2011). Proposals to explain asymmetries among unattested onsets, and unattested structures more generally, have argued that these asymmetries arise (i) from universal grammatical principles, such as the sonority hierarchy (Selkirk 1984;Clements 1990), (ii) from the formal properties of phonological learning that allow abstraction from the lexicon, and/or (iii) from detailed knowledge of perceptual and articulatory structures.…”
Section: Sources Of the Identity Preferencesupporting
confidence: 90%
See 2 more Smart Citations
“…The identity preference in CQ speakers found here is consistent with previous work that shows a correlation between typology and synchronic asymmetries in individual speakers, particularly work examining sonority profiles in onsets (Greenberg and Jenkins 1964;Scholes 1966;Broselow and Finer 1991;Coleman and Pierrehumbert 1997;Moreton 2002;Davidson 2006Davidson , 2010Berent et al 2007;Berent and Lennertz 2010;Daland et al 2011). Proposals to explain asymmetries among unattested onsets, and unattested structures more generally, have argued that these asymmetries arise (i) from universal grammatical principles, such as the sonority hierarchy (Selkirk 1984;Clements 1990), (ii) from the formal properties of phonological learning that allow abstraction from the lexicon, and/or (iii) from detailed knowledge of perceptual and articulatory structures.…”
Section: Sources Of the Identity Preferencesupporting
confidence: 90%
“…The current study contributes to the body of research documenting a correlation between typology and synchronic grammars (Greenberg and Jenkins 1964;Broselow and Finer 1991;Broselow et al 1998;Berent et al 2007;Berent and Lennertz 2010), and investigating the sources of such effects in detailed generalization from the lexicon (Daland et al 2011) and/or learned interpretation of phonetic properties (Davidson and Shaw 2012). Accounts of the current findings based on either lexical generalization or phonetic preferences are presented, though the data do not conclusively choose between these explanations.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…No clear case can be made for the relative markedness of the liquids /l/ or /r/ ͑Bhat, 1974; Maddieson, 1984͒. However, it was possible to assign markedness values to items for the range of consonant clusters included in this experiment, based upon proposals by Broselow andFiner ͑1991͒ andIverson ͑1993͒. Finally, the perceptual demands of the listening task ͑factor 4, Table I͒ exercise a degree of control over listeners' perceptual responses and the foregrounding or backgrounding of factors mentioned above. Mochizuki ͑1981͒ found that Japanese listeners' ability to discriminate and label minimal pair /l-r/ contrasts presented in triadic comparisons was highly dependent on the echoic memory load induced by the response task.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Broselow and Finer (1991) Carlisle ( , 1991Carlisle ( , 1992Carlisle ( , 1994Carlisle ( , 1997Carlisle ( , 2006 examined the acquisition of some English onsets, /sl, s+nasal, s+stop/, by speakers of Spanish, a language that disallow initial /s/ clusters. Generally, it was expected that these clusters would be problematic for Spanish speakers learning English.…”
Section: Sonority Sequencing Principle (Ssp)mentioning
confidence: 99%